The Kajian User Experience Media Literasi Visual Buku Cerita Anak Berbasis Augmented Reality - Putri, Kinanti Erste Panggayuh; Deny Tri Ardiyanto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2024)
Virtual reality and the real world are combined in the Augmented Reality Children Storybook (ARCS), a visual literacy media of the Timun Mas folk tale. This study examines how parents and kindergarten instructors use ARCS Timun Mas, which uses augmented reality as a narrative tool for young children, in order to put the idea of smart education into practice. The case study explorative qualitative research method was used to dig deeper through the study of works and audience studies through the results of the User experience questionnaire (UEQ), which considers 6 measurement indicators (visual appeal, clarity of storyline, media efficiency, media reliability, technology simulation, and media novelty). The findings demonstrated that ARCS Timun Mas media has a lot of potential for use as a technology-based visual literacy media innovation in early childhood as a unit facility since it can offer a fresh, more engaging visual experience by combining visual illustrations, 3D animation, and audio narration. Further research suggestions can be carried out with direct involvement of children to examine the role of ARCS visual media in the formation of visual perception and reception of visual messages in the form of educational and moral values.